Giant serous cystadenoma. Report of a case. - Bendezú, Guido (2015)
For serous ovarian cystadenoma uncommon in our environment because of its size and weight, removed in the Department of Obstetrics and Gynecology Hospital Torrealva Felix Gutierrez, EsSalud of Ica presents. Patient 47, illiterate workers, a native of Abancay, with a history of primary infertility, box bloating and abdominal pain for eight years. Giant diagnosed with ovarian tumor, is subjected to surgery. High in good condition. Prosterior control without complications.